WHAT EFFECTIVE LANGUAGE TEACHERS DO: A CASE STUDY OF 5 HIGH-ACHIEVING UNIVERSITY SPANISH INSTRUCTORS - Borden, Rebecca (My University, 2017)
The quality of instruction in foreign language classes can be widely variable. The purpose of this qualitative case study was to uncover the approaches to instruction enacted by five high-achieving university Spanish instructors at a doctoral-level university in the southwestern United States. Findings indicate that high-achieving university Spanish instructors shared the traits of enthusiasm, clarity, high levels of student engagement, well-established control, and care. Embedded in these behaviors, high-achieving instructors were observed to employ the use of activities that developed communicative competence. A strong emphasis on speaking and listening in the target language, and some aspects of Task-based Language Teaching were also evident, although specific approaches in each of these areas varied by instructor based on language background and teaching philosophy. Student-performance in courses taught by high-achieving instructors was significantly higher in all four skill areas—reading, writing, speaking, and listening—than the performance of students in courses taught by low-achieving instructors. Findings support the notion that approaches to instruction have a palpable, practical impact on student learning. Engaging courses and caring instructors contributed to positive language-learning experiences and relatively higher levels of learning.
Keywords: Language Teacher Effectiveness, Foreign Language in Higher-Education, Self-efficacy, ACTFL in Higher-Ed